Functionalization of Magnetic Nanoparticles with Organic Ligands toward Biomedical Applications. Issue 5 (22nd February 2021) - Yang, Hong Yu; Li, Yi; Lee, Doo Sung
Abstract : Functionalization of magnetic nanoparticles (MNPs) with organic ligands to prepare personalized nanomedicine has attracted tremendous attention in biomedical applications. These organic/MNP nanohybrid platforms not only can exert the superparamagnetic property of MNPs for diagnosis imaging and treatment, but are also endowed with the merits of organic ligands for improved tumor‐targeting ability, blood circulation time, and cellular uptake. Flexibly manipulating the interactions between different inorganic ligands and MNPs to establish a single MNP matrix or multiple MNP assemblies presents advanced strategies in controlling their composition and chemical–physical and biological properties for various biomedical applications. Beginning with a brief introduction to a variety of strategies for the efficient functionalization of MNPs with various organic ligands, herein, the recent progress in the development and biomedical applications of the different types of nanoplatforms of organic ligand–mediated MNPs is briefly introduced, including diagnosis, therapy, imaging‐guided therapy, and drug delivery. Finally, the future opportunities and challenges for next‐generation high‐performance organic ligand–functionalized MNP nanoplatforms are also discussed. Abstract : Magnetic nanoparticles can be engineered with different organic ligands, including small molecules, biomolecules, and synthetic polymers, for biomedicine applications by applying various preparation methods. Herein, recent innovations in and future challenges to the integration of MNPs and organic ligands for enhancing diagnosis imaging and therapy as well as controlling drug delivery are introduced.